POTENTIAL OF JIRINGA AS ORGANIC HERBICIDE - Ikhsan Hasibuan (University of Prof. Dr. Hazairin, SH, 2016)
Jiringa is one potential plants to be developed as organic herbicide since its toxic compounds. Some researches found that extract of this plant contained fenolic, flavonoid and carbolic acid. Thus, it is able to inhibit weed growth. This research was conducted to evaluate the ability of jiringa seed pod extract as organic herbicide. Five levels of extract concentration had been done: 100%, 75%, 50%, 25% and 0% and control. Each treatment sprayed on one month old weeds that grown on trays of 30 x45 cm. The results showed that number of weed killed by jiringa extract can be found at 7 days atfer treatment (DAT) and reduced by days of 14 and 21. Thus, we know that the mode of action of jiringa extract is contact herbicide. At 7 DAT, extract concentration 50% and above were able to control weeds more than 88%. However at 14 DAT, only extract concentration 75% and above were able to do that. Unfortunately, at 21 DAT, no treatment was able to control weed well (above 80% weed death). In addition, extract concentration of 75% and 100% reduced weed biomas to 50% and76% respectively. This research supported previous researches which concluded that jiringa extract was able to control weed growth.